Anti-cancer effect of naringenin chalcone is mediated via the induction of autophagy, apoptosis and activation of PI3K/Akt signalling pathway (Bangladesh Journal of Pharmacology, 2016)
The aim of the current study was to investigate the in vitro and in vivo anti-tumor effects of naringenin chalcone in U87MG human glioblastoma cells and in xenograft mice model. The effect of naringenin chalcone on apoptosis induction was assessed by fluorescence microscopy using acridine orange/ethidium bromide and Hoechst 33342. Effect of the compound on PI3K/Akt signalling proteins was assessed by Western blot assay. Naringenin chalcone induced dose-dependent as well as time-dependent cytotoxic effects in these cells. Transmission electron microscopy showed that naringenin chalcone induced the formation of autophagic vacuoles. The number and size of these autophagic vacuoles increased with increasing dose of naringenin chalcone. It also led to the activation of both phosphorylated as well as non-phosphorylated PI3K and Akt proteins. In vivo results showed that both tumor volume and tumor weight were lesser in naringenin chalcone-treated groups with its different doses than in vehicle control group.Video Clip of Methodology:Cell proliferation assay: 1 min 08 sec   Click to watch